POTENT ANTICANDIDAL ACTIVITY OF THE METHANOLIC EXTRACT OF WEDELIA CHINENSIS LEAVES (OSBECK) AGAINST PATHOGENIC CANDIDA ALBICANS - DARAH IBRAHIM,; LIM SHEH HONG,; NINTHIANANTHAM KUPPAN, (International Journal of Pharma and Bio Sciences, 2013)
The anticandidal activity of the methanolic extract of Wedelia chinensis leave was studied and tested against four pathogenic Candida albicans strains of clinical isolates. The extract exhibited favorable anticandidal activity with the zones of inhibition between 18.00 ± 0.10 to 20.00 ± 0.17 mm and minimum inhibition concentration (MIC) values between 3.13 and 6.25 mg/mL. The time-kill studied of the extract against the selected strain, C. albicans 1 suggested that the extract possessed yeastocidal properties at higher concentrations and eradicated the growth of yeast cells. The SEM and TEM micrographs exhibited major abnormalities occurred on the yeast cells after exposed to the extract were complete alterations in their morphology and collapsed of the cells beyond repair. The methanolic extract of W. chinensis may be an effective anticandidal agent to treat pathogenic yeast infections such as candidiasis.